Hydroisomerization of Emerging Renewable Hydrocarbons using Hierarchical Pt/H‐ZSM‐22 Catalyst. Issue 3 (15th January 2013) - Martens, Johan A.; Verboekend, Danny; Thomas, Karine; Vanbutsele, Gina; Gilson, Jean‐Pierre; Pérez‐Ramírez, Javier
<x xml:space="preserve">Abstract</x> Last site standing: A new generation of hierarchical Pt/H‐ZSM‐22 zeolites is designed for the efficient processing of upcoming renewable feedstocks. The enhanced accessibility of the active sites is vital for the superior activity and exceptional selectivity in the hydroisomerization of model molecules such as nonadecane and pristane.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>